Cambios fisicos y quimicos durante la maduracion del fruto del cafe - Marin-Lopez, S.M.=700 1 Arcila-Pulgarin, J.; Montoya-Restrepo, A.C.
(Es)
ilus., 20 ref.
Keywords: COFFEA ARABICA; FRUTO; PROPIEDADES FISICO-QUIMICAS; MADURACION; COLOMBIA